Real-World Practice Patterns and Predictors of Continuous versus Intermittent Androgen Deprivation Therapy Use for Prostate Cancer in Older Men. Issue 4 (25th October 2021) - Cheung, D. C.; Alibhai, S. M. H.; Martin, L. J.; Komisarenko, M.; Dharma, C.; Warde, P.; Sridhar, S. S.; Fleshner, N. E.; Kulkarni, G. S.; Finelli, A.
Abstract : Purpose: Phase-III randomized control trial evidence suggests intermittent androgen deprivation therapy (IADT) is not significantly inferior to continuous androgen deprivation therapy (ADT) for patients with prostate cancer (PC). However, clinical practice and guidelines differ in their recommendations. We evaluate real-world utilization and practice patterns of IADT. Materials and Methods: Ontario men ≥65 years of age with PC who initiated ADT for ≥3 months were identified (1997–2017). Lapses in ADT ≥6 months (initial gap) and ≥3 months (subsequent gaps) were used to classify IADT. Neoadjuvant/adjuvant therapy was excluded. Disease stage adjustment was completed for patients with likely metastatic disease based on de novo presentation with ADT. Patient and physician predictors of IADT were analyzed using multivariable logistic regression. Results: We identified 8, 544 patients with 1, 715 having previously received local therapy. Among all patients, 16.4% received IADT. This ranged from 11.4%–24.8% across health-planning regions and increased to 26.6% in those with previous local therapy. Mean followup was 8.3 years. Patients with prior local therapy (OR 1.85, 95% CI 1.59–2.17, p <0.001) and those in the highest income quintile (OR 1.32, 95% CI 1.08–1.60, p=0.005) had increased odds of receiving IADT. Radiation oncologists were more likely to use IADT than urologists (OR 1.99, 95% CI 1.59–2.50, p <0.001), as were physicians with more experience (≥10 years in practice: OR 1.44, 95% CI 1.11–1.88, p=0.007). In specialty-stratified analyses, case volume was significantly associated with IADT for radiation oncologists (highest quartile: OR 1.73, 95% CI 1.14–2.62, p=0.009). Conclusions: IADT remains underutilized for patients with PC who ≥65 years of age with only 1 in 4 to 1 in 6 eligible patients receiving this form of care. Clinical, sociodemographic and physician characteristics play an important role in treatment selection.